Expression of IFN‐γ, IL‐4, and IL‐17 in cutaneous schistosomal granuloma. (6th March 2014) - Attia, Sameh K.; Moftah, Noha H.; Abdel‐Azim, Eman S.
Abstract Objectives Cutaneous schistosomal granuloma (CSG) is a rare dermatological disease, the clinical and histopathological features of which are well defined. Although a panoramic picture of its immunopathogenesis in humans is not yet available, it is believed to be induced by T helper 1 (Th1), Th2, or Th17 cytokines in animals. This study evaluated the expression of different types of Th cytokines, including Th1 cytokine interferon‐γ (IFN‐γ), Th2 cytokine interleukin‐4 (IL‐4), and Th17 cytokine IL‐17, in human CSG. Methods This study included nine patients with CSG. Dermatological examinations were conducted in all subjects. Skin biopsy specimens were stained with hematoxylin and eosin (H&E). Immunohistochemical examination was performed using three monoclonal anti‐human antibodies against IFN‐γ, IL‐4, and IL‐17 to evaluate Th1, Th2, and Th17 cytokines, respectively. Results The most common site of CSG manifestation was the paraumbilical area, which was affected in 66.7% of patients. All lesional skin biopsy specimens revealed multiple dermal granulomas surrounding schistosomal eggs. Positive immunoreactivity for IFN‐γ, IL‐4, and IL‐17 was present in dermal inflammatory infiltrate in 88.9, 11.1, and 88.9% of subjects, respectively. There were statistically significant negative correlations between the duration of disease and both IFN‐γ and IL‐17 (P ≤ 0.05), and a statistically significant positive correlation between IFN‐γ and IL‐17 (P ≤ 0.05). Conclusions This study suggests that CSG is formed by the action of both Th1 (IFN‐γ) and Th17 (IL‐17) cytokines, which have been shown to be directed against the schistosomal egg to induce a cell‐mediated immune response.